The Effect of Pungent and Tingling Compounds from Piper nigrum L. on Background K+ Currents - Beltrán, Leopoldo R.; Dawid, Corinna; Beltrán, Madeline; Levermann, Janina; Titt, Sascha; Thomas, Sini; Pürschel, Viktoria; Satalik, Miriam; Gisselmann, Günter; Hofmann, Thomas; Hatt, Hanns (Frontiers in Pharmacology, 2017)
Black peppercorns (Piper nigrum L.) elicit a pungent and tingling oral impression. Their pungency is partially explained by the agonist activity of some of their active principles, especially piperine, on TRP channels. However, we recently showed that piperine, as well as other pungent compounds, also possess a marked effect on two-pore domain (KCNK, K2P) K+ channels. Members of this family play a key role in maintaining the resting membrane potential of excitable cells. Interestingly, tingling compounds have been shown to induce neuronal excitation by inhibiting KCNK channels. We addressed the question of whether it was plausible that KCNK channels could constitute a physiologically relevant target for the sensory active compounds present in black peppercorns. Because previous studies have demonstrated that mouse trigeminal neurons respond to several pungent compounds, to which humans are also sensitive, we used a primary culture of mouse trigeminal neurons to investigate whether the effect of piperine on these cell types could also be mediated by KCNK channels. We observed that even in the presence of classical TRP-antagonists, piperine was still able to activate a fraction of trigeminal neurons. Furthermore, our results showed that piperine is capable of inducing neuronal depolarization by a mechanism that does not require extracellular Na+ or Ca2+. This depolarization was mediated by the inhibition of a background K+ conductance, most likely corresponding to the KCNK channels of the TASK subfamily. We then performed a screening with 12 other pungent and/or tingling chemosensates isolated from black peppercorns. These compounds were evaluated on Xenopus laevis oocytes expressing the human orthologues of KCNK3, KNCK9 and KCNK18, which we previously showed to be inhibited by piperine. Remarkably, almost all of the isolated chemosensates inhibited the basal activity of hKCNK3, with 1-(octadeca-2E,4E,13/12Z-trienoyl)pyrrolidine acting as one of the most potent natural blockers for hKCNK3 found to date. Our results suggest that KCNK channels, especially KCNK3, are likely to play a complementary role to TRP channels in the complex orosensory impression elicited by black peppercorns, while they also help to expand the pharmacological knowledge of KCNK channels.